æƒ…æ™¯æ•™å¦æ³•å¯¹ä¸¹å¤§ä¸æ–‡ç³»2015 å±ŠAçå¦ç”Ÿç†è§£â€œæŠŠâ€å—å¥çš„å½±å“ - Rini, Yuni Pustia (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Â AbstractBa sentence is one of the charateristic sentence, because indonesian languange has no â€œBaâ€ sentence is also one of the difficulties for learner so to help student in understanding the usage of â€œBaâ€ sentences. The writer use â€œsituasional methodâ€ in doing search to the students of Tanjungpura University, Education and Teaching Faculty , Mandarin Major 2015 class A. In the process of research, the writer has used video and picture in explaning â€œBaâ€ sentence to students after doing research, the writer conclude as a whole, students in understanding the usage of â€œBaâ€ sentence most has already reacher more than 60%, this shows use â€œsituasional Methodâ€ help students in understanding â€œBaâ€ sentence effectively. Though the writerâ€™s experiment teaching using â€œsituasional Methodâ€ could deeper students learning of â€œBaâ€ sentence and also the error of using sentence has decreased. Keywords: â€œBaâ€ sentence Â Situasional MethodÂ